Occupational hazards to dental staff - Jamshid Ayatollahi; Fatemah Ayatollahi; Ali Mellat Ardekani; Rezvan Bahrololoomi; Jahangir Ayatollahi; Ali Ayatollahi; Mohammad Bagher Owlia (Dental Research Journal, 2012)
Dental professionals are predisposed to a number of occupational hazards. These include exposure to infections (including Human Immunodeficiency Virus and viral hepatitis); percutaneous exposure incidents, dental materials, radiation, and noise; musculoskeletal disorders; psychological problems and dermatitis; respiratory disorders; and eye insults. Percutaneous exposure incidents remain a main concern, as exposure to serious infectious agents is a virtual risk. Minimizing percutaneous exposure incidents and their consequences should continue to be considered, including sound infection control practices, continuing education, and hepatitis B vaccination. Basically, for any infection control strategies, dentists should be aware of individual protective measures and appropriate sterilization or other high-level disinfection utilities. Strained posture at work disturbs the musculoskeletal alignment and leads to stooped spine. The stooped posture also involved certain groups of muscles and joints. This may lead to diseases of the musculoskeletal system. Continuous educating and appropriate intervention studies are needed to reduce the complication of these hazards. So, it is important for dentists to remain constantly up-to-date about measures on how to deal with newer strategies and dental materials, and implicates the need for special medical care for this professional group.